The assessment of ecological plasticity and stability of winter barley varieties and lines - E. G. Filippov; A. A. Dontsova; R. N. Bragin (Зерновое хозяйство России, 2018)
The assessment of ecological plasticity and stability of winter barley varieties and lines Barley is one of the main grain crops. Selection of winter barley in the Rostov region is conducted in the following areas: high yield, winter resistance, resistance to lodging and diseases, etc. For this purpose, there was an assessment of the ecological plasticity and stability of winter barley varieties and lines. In the study, there were used 14 winter barley varieties developed in the FSBSI ‘ARC ‘Donskoy’. The evaluation was carried out according to the method of S.A. Eberchart, W.A. Rassel (1966) in V.A. Zykin's edition, using the programs for statistical processing Excel and Statistica 10. As a result of the analysis, the varieties ‘Tigr’, ‘Vivat’, ‘Timofey’, ‘Marusya’, ‘Parallellum 1967’ possess ecological plasticity, and the varieties ‘Erema’, ‘Master’ and ‘Pallidum 1952’ are possess responsiveness to the improvement of the conditions of cultivation. The varieties ‘Marusya’ and ‘Parallellum 1962’ proved to be the best among the studied varieties and lines. Their regression lines are at the average level, but the highest average yield in relation to other varieties indicates a stable yield under different growing conditions. In the formation of productivity, the factor "year" played the main role (98.6%). This index is explained by the fact that during the years of research (2015-2017) the productivity of winter barley was strongly influenced by environmental conditions.